2017
DOI: 10.12775/llp.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Logic, Reasoning, Argumentation: Insights from the Wild

Abstract: Abstract. This article provides a brief selective overview and discussion of recent research into natural language argumentation that may inform the study of human reasoning on the assumption that an episode of argumentation issues an invitation to accept a corresponding inference. As this research shows, arguers typically seek to establish new consequences based on prior information. And they typically do so vis-à-vis a real or an imagined opponent, or an opponent-position, in ways that remain sensitive to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Thus, the persuasive agenda of the narrative was not that different from the goal of a sermon. As the preacher declares, he seeks to "tend to the Glory of our Redeemer, and the Increase of his Triumphs, carrying on of the Design of said History, containing Accounts of the Revival and Propagation of Religion in this remarkable Day of Grace" (7). Blair's perspective is that of the sacred history-in which the revival is an event that propels the advancement of religion in the period before the second coming of Christ and messianic deliverance.…”
Section: Samuel Blair's Revival Accountmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the persuasive agenda of the narrative was not that different from the goal of a sermon. As the preacher declares, he seeks to "tend to the Glory of our Redeemer, and the Increase of his Triumphs, carrying on of the Design of said History, containing Accounts of the Revival and Propagation of Religion in this remarkable Day of Grace" (7). Blair's perspective is that of the sacred history-in which the revival is an event that propels the advancement of religion in the period before the second coming of Christ and messianic deliverance.…”
Section: Samuel Blair's Revival Accountmentioning
confidence: 99%
“…Of the three, the time honored rite permeated the neo-conservative revision of the past, bypassing anything slightly hinting at niebłagonadiożnost (political incorrectness). 7 6…”
Section: Work Citedmentioning
confidence: 99%
See 2 more Smart Citations
“…Viewing arguments as organisms, Toulmin (1958Toulmin ( [2003) 13 observed that different fields use distinct argument evaluation criteria, but the same argument layout, or model (Conley 1990, 294-296;Hitchcock and Verheij 2006;van Eemeren et al 2014, 203-256;Zenker 2018). In fact, Toulmin's model became so influential as to widely "replace the old concepts of 'premises' and 'conclusion' with the new concepts of 'claim', 'data', 'warrant', 'model qualifier', 'rebuttal' and 'backing'" (van Eemeren et al 2014, 204).…”
Section: The Toulmin Modelmentioning
confidence: 99%